Testing the Mediating Role of Student Engagement: Self-‎Efficacy, Learning Motivation, and Examination Performance ‎in Indonesian Vocational High Schools - Tristin Emilda; Dessi Susanti (JPI: Jurnal Pustaka Indonesia, 2026)
Academic underachievement in Indonesian vocational high schools (SMK) is often attributed to cognitive ability alone, yet non-cognitive factors may matter. Drawing on Bandura's social cognitive theory and Astin's involvement theory, this study tested whether student engagement mediates the associations of self-efficacy and learning motivation with examination performance. A cross-sectional survey was administered to 282 students in four state vocational high schools in Pesisir Selatan Regency, West Sumatra, sampled proportionately by school. Constructs were modelled as reflective-reflective higher-order constructs and estimated with the disjoint two-stage approach in PLS-SEM; performance was a single summative examination score drawn from school records and not equated across the four schools. After item purification the engagement construct retained only its behavioural and emotional dimensions, so H5 to H7 test a narrower construct than the introduction describes. Discriminant validity was not established for the self-efficacy and engagement pair (HTMT = .908, above the pre-specified .90). Self-efficacy (β = .640, 95% CI [.537, .743]) and learning motivation (β = .141, 95% CI [.027, .255]) were associated with engagement, explaining 55.7% of its variance. No path reached examination performance: the model explained essentially none of its variance (R² = .005, adjusted R² = -.006), and all three paths were statistically equivalent to zero within ±.20. Five hypotheses were not supported. The null result is consistent with criterion misalignment, but the design did not test that explanation.